Transforming organic waste into compost: An integrative approach to sustainable agriculture - Mustari, Sahdan; Yusriyanto (EcoVision: Journal of Environmental Solutions, 2025)
Background: Pangkajene and Islands Regency (Pangkep) has a unique geographical character that combines the karst foothills of Pangkep–Maros with a cluster of islands in the Makassar Strait. This condition has given rise to an economy based on agriculture, fisheries, and industry, but on the other hand, it has also created waste management issues, particularly with regard to organic waste from households and traditional markets, which has the potential to cause odours, leachate, and greenhouse gas emissions if not managed properly. Method: The study used a descriptive-exploratory qualitative approach with an embedded case study. The main "case" was the ecosystem of organic waste utilisation for compost in Pangkep. Findings: This study shows that organic waste is still the dominant fraction in Pangkep Regency, but its management is not yet optimal, causing environmental problems such as odour, leachate, and potential greenhouse gas emissions. Conclusion: This study confirms that organic waste in Pangkep Regency has great potential to be processed into compost, but its utilisation is still far from optimal. Novelty/Originality of this article: The originality or uniqueness of this article lies in its focus, which not only discusses organic waste management as an environmental issue, but also directly links it to the needs of sustainable agriculture in Pangkep Regency. This article presents an integrative approach by combining the potential of municipal waste and rice straw as compost raw materials, while also assessing product quality based on the SNI 7763:2018/2024 standard.